2017
DOI: 10.2320/matertrans.m2017103
|View full text |Cite
|
Sign up to set email alerts
|

Fundamental Properties of Ti-6Al-4V Alloy Produced by Selective Laser Melting Method

Abstract: This study was conducted to comprehensively investigate the fundamental properties of Ti-6Al-4V alloy produced by the selective laser melting (SLM) method. The examined materials were three SLM materials having different axial directions. For comparison, wrought material of Ti-6Al-4V alloy was also examined. The results showed that the densities of the SLM materials were adequately high and more than 99.9% of that of the wrought material. The SLM materials possessed a columnar microstructure extending along th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…This is due to the martensitic transformation owing to water-quenching. In a previous study, 16) we reported on the possibility that fine ¢ phase exists in the dark area of the phase map. Thus, it is inferred that the ¢ phase was generated in the fine acicular ¡A phase.…”
Section: Resultsmentioning
confidence: 93%
“…This is due to the martensitic transformation owing to water-quenching. In a previous study, 16) we reported on the possibility that fine ¢ phase exists in the dark area of the phase map. Thus, it is inferred that the ¢ phase was generated in the fine acicular ¡A phase.…”
Section: Resultsmentioning
confidence: 93%
“…For comparison, we referred to our previous study concerning the XRD profiles, the Vickers hardness, the mechanical properties, the S-N plots and the observation results of the fracture surfaces of the wrought material (hereafter W material) and the UN material. 28) In addition, the W material was annealed at 1023 K for 3.6 ks before the tests. For reference, its chemical compositions are shown in Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…3). Based on the previous study, 28) the dark regions in the phase map of the UN material were considered to mainly be composed of the metastable ¢ phase. However, no peaks of the ¢ phase were found in the XRD profile of the UN material (Fig.…”
Section: Microstructuresmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, more and more attention has been attracted on additive manufacturing (AM) technology due to its solid freeform fabrication, material saving, time saving and so on. [1][2][3][4][5] Selective laser melting (SLM), which is one of additive manufacturing technology, has got notice from a series of industries like military field, automotive field and aerospace field as it can achieve the formation of the metal part. [6][7][8][9][10] What's more, as the layer by layer forming from the bottom of the manufactured part, this method makes it possible to manufacture any complex structure part in theory.…”
Section: Introductionmentioning
confidence: 99%